Idionyx (Odonata: Corduliidae) of the Western Ghats with a description of a new species - Subramanian, K. A.; Rangnekar, Parag; Naik, Rohan (Zootaxa, 2013)
The status and distribution of Idionyx Hagen, 1867 (Odonata: Corduliidae), of the Western Ghats, India, is updated and a new species Idionyx gomantakensis is described and illustrated based on male and female specimens from Kulem (=Col-lem), Goa, India. This new species can be differentiated from other species of Idionyx by long and slender cerci and epiproct, absence of teeth in the basal half of the cerci, and a tuft of golden hairs at the end of the lateral lobes of the epiproct. A revised key to the species of the genus is provided, and its diversity and ecology in the Western Ghats is dis-cussed.